Effectiveness of Small-bore Ambulatory Pleural Drain in Treatment of Pneumothorax and Haemothorax - E., Ekpe E.; F., Uduma; V., Umoh; M. C., Ikpe; S. C., Eyo; A. F., Akpan (International Journal of Innovative Research in Medical Science, 2019)
Background: Pleural drainage is a life-saving procedure that is commonly performed to evacuate pleural collection of air or liquid from traumatic or non-traumatic causes. The pleural tube drain is commonly connected to underwater seal bottle thereby limiting the movement of the patients with attendant risks of immobilisation. There are reports of pleural drainages utilising small bore pleural drains attached to drainage bag and asserted to be as effective as large bore thoracic catheter connected to underwater seal bottle. In addition to the reported effectiveness of small bore ambulatory pleural drainage, the risks of prolonged immobilisation are mitigated, and there is saving of costs. Literature search has not revealed any comparison of the two pleural drainage systems in Nigeria, hence this index study. Objective: To compare the pleural drainage characteristics of small bore pleural drains attached to drainage bag with those of large bore thoracic catheters connected to underwater seal bottle in the management pneumothorax and haemothorax. Results: Among patients with pneumothorax, 66.7% of conventional group and 100% of small bore group regained normal respiratory rate before removal o pleural drain, although at 30 days post drainage check all n the two groups were normal. Using oxygen saturation (SpO2), conventional drainage system was initially better (66.7% vs 25% p<0.0001), later inferior (83.3% vs 100%), and finally same at follow-up (100% vs 100%). Lung re-expansion was also initially better in the conventional drainage group at 30 minutes following commencement of pleural drainage than in the small bore pleural drain group (66.7% vs 50.0%), but afterward became complete in all patients in the two groups before removal of pleural drain and at 30 days follow up. Duration of pleural drainage and length of hospitalisation were shorter in more patients in the small bore group than in the large bore group (p=0.571). In the patients with haemothorax, there was no statistically significant difference in any outcome measure among the groups. Conclusion: The use of small bore pleural drains was as equally effective as the use of large bore chest tubes in the management of pneumothorax and haemothorax.